Godetia : a source of natural dyes - Singh, Babita; Jain, Ritu; Sindhu, S S; Yadav, Harendra; Kumar, Raman (Indian Horticulture, 2019)
Godetia is a beautiful bedding plant and can be used as cut flower, but vaselife of this flower is very less. Besides, it can be used in value-addition by making dry flower products and extracting natural dyes. Use of synthetic dyes results in environmental pollution and allergies like dermatitis, asthma, bronchitis etc. Therefore, natural dyes extracted from plants can be used to avoid these problems. Moreover, many countries have imposed stringent environmental standards due to toxic and allergic reactions associated with synthetic dyes. Nature has gifted us more than 500 dye-yielding plant species. Most of the work on extraction of natural dyes have been done using fruits and vegetables, since the flowers are non edible, therefore they can be subjected to the extraction of natural dyes. Therefore, the dyeing pigments present in flowers of pink godetia were extracted by using four different solvent extraction method (alkaline, acidic, alcoholic and aqua) to evaluate the best extraction method. Three different mordants were used to set isolated dye on cotton fabric by forming a co-ordination complex. Dye extracted from pink godetia flower can be used for colouration of fabrics, tinting of dry flowers, paper printing ink, leather, cosmetics, paint industries and preparation of other value added products.